International sale of goods: effects of failure to notify by the receiving party within the time limit of non-conformity on the goods in the light of the Vienna Convention of 11th April 1980 - Gómez Ferreres, Montse (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This work analyzes the most controversial issues of Private International Law in the sentence issued by the Civil Chamber of the Supreme Court number 2282/2020, of July the 6th, solving the appeal in cassation filed by the Spanish company Ingeniería y Tratamiento de Valorización S.L, The German company Econ Industries GMBH was the party appealed against, in which the interpretation of the United Nations Convention of 11th April 1980 on Contracts for the International Sale of Goods was raised, which, in order to exercise the rights it recognizes for the buyer, imposes on it the burden of communicating to the seller both the lack of conformity with the goods received and the termination of the contract “within a reasonable time”.